2009
DOI: 10.1194/jlr.m800439-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Genetic inactivation of NPC1L1 protects against sitosterolemia in mice lacking ABCG5/ABCG8

Abstract: Mice lacking Niemann-Pick C1-Like 1 (NPC1L1) (NPC1L1 2/2 mice) exhibit a defect in intestinal absorption of cholesterol and phytosterols. However, wild-type (WT) mice do not efficiently absorb and accumulate phytosterols either. Cell-based studies show that NPC1L1 is a much weaker transporter for phytosterols than cholesterol. In this study, we examined the role of NPC1L1 in phytosterol and cholesterol trafficking in mice lacking ATP-binding cassette (ABC) transporters G5 and G8 (G5/G8 2/2 mice). G5/G82/2 mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 59 publications
5
42
0
Order By: Relevance
“…Another protein that is expressed exclusively in the same two cell types is acyl CoA:cholesterol acyltransferase type 2 (ACAT2), a cholesterol-esterifying enzyme residing in the endoplasmic reticulum (ER) membrane ( 12 ). Mice lacking G5G8 have phenotypes resembling patients with sitosterolemia, including increased fractional absorption of noncholesterol sterols, marked accumulation of sitosterol and campesterol in the blood and liver, reduced levels of biliary cholesterol, and various hemolytic disorders ( 7,13 ). These fi ndings suggested that the physiological role of G5G8 is to limit phytosterol accumulation in the body by limiting its absorption in the intestine and by promoting its secretion from the liver.…”
Section: G5g8mentioning
confidence: 86%
See 1 more Smart Citation
“…Another protein that is expressed exclusively in the same two cell types is acyl CoA:cholesterol acyltransferase type 2 (ACAT2), a cholesterol-esterifying enzyme residing in the endoplasmic reticulum (ER) membrane ( 12 ). Mice lacking G5G8 have phenotypes resembling patients with sitosterolemia, including increased fractional absorption of noncholesterol sterols, marked accumulation of sitosterol and campesterol in the blood and liver, reduced levels of biliary cholesterol, and various hemolytic disorders ( 7,13 ). These fi ndings suggested that the physiological role of G5G8 is to limit phytosterol accumulation in the body by limiting its absorption in the intestine and by promoting its secretion from the liver.…”
Section: G5g8mentioning
confidence: 86%
“…These fi ndings suggested that the physiological role of G5G8 is to limit phytosterol accumulation in the body by limiting its absorption in the intestine and by promoting its secretion from the liver. Because sitosterolemic patients and G5G8 knockout (G5G8 Ϫ / Ϫ ) mice can still maintain the same rank order of absorption effi ciency (cholesterol > campesterol > sitosterol), it has been suggested that other proteins independent of G5G8 are responsible for the selectivity of cholesterol over phytosterol absorption ( 13,14 ).…”
Section: G5g8mentioning
confidence: 99%
“…After 18 weeks on an HFD, mice were used for the determination of fecal neutral sterol excretion and intestinal cholesterol absorption as we have described previously ( 28 ).…”
Section: Fecal Neutral Sterol Excretion and Intestinal Cholesterol Abmentioning
confidence: 99%
“…For example, the dietary sterol intake may influence the plasma sterol levels, although the two patients lived in the same household and reported consuming a similar diet. Animal studies shown that the genetic inactivation of NPC1L1 protects against sitosterolaemia in mice lacking Abcg5/Abcg8 15) . In humans, rare variants in NPC1L1 have been reported to be associated with reduced sterol absorption and plasma LDL-C levels 16) .…”
Section: Molecular Geneticsmentioning
confidence: 99%